2009
DOI: 10.1021/jo9012699
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Promoted and -Controlled Aza-Michael Reaction with Aromatic Amines

Abstract: 1,4-Addition of anilines onto Michael acceptors proceeds easily in specific polar protic solvents, without any promoting agent. According to the solvent and to the electrophile, the selectivity of the reaction can be finely tuned. With methyl acrylate as electrophile, only monoaddition takes place in water, while the diadduct is yielded in hexafluoroisopropyl alcohol (HFIP). The use of methyl vinyl ketone as a partner affords the monoadduct in water, the diadduct in trifluoroethanol (TFE), and the quinoline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 11 publications
1
61
0
2
Order By: Relevance
“…Reports of aza-Michael additions occurring in water indicated that the desired 8 could be synthesised under mild conditions, and we therefore decided to adapt these published conditions to larger scale work [2526]. Initial attempts involving a 1:1 molar mixture of o -toluidine ( 5 ) and methyl vinyl ketone (MVK) indicated that only around 60% of the starting aniline had converted, particularly at larger scales (>1 g).…”
Section: Resultsmentioning
confidence: 99%
“…Reports of aza-Michael additions occurring in water indicated that the desired 8 could be synthesised under mild conditions, and we therefore decided to adapt these published conditions to larger scale work [2526]. Initial attempts involving a 1:1 molar mixture of o -toluidine ( 5 ) and methyl vinyl ketone (MVK) indicated that only around 60% of the starting aniline had converted, particularly at larger scales (>1 g).…”
Section: Resultsmentioning
confidence: 99%
“…The highly electrophilic character of the carbonyl group attached to CF 3 is probably enhanced by the high hydrogen bond donating ability of the fluorinated solvents, which causes the rate of the attack of the hydrazine NH 2 group to be faster than the other carbonyl group, COAr ( Figure 2). A c c e p t e d M a n u s c r i p t 12 The same group also reported the synthesis of a series of quinoline from the reaction of methyl vinyl ketone (MVK) with electron-rich anilines under reflux condition (Scheme 7) [38]. Recently, Saito, Hanzawa, and co-workers described the tandem approach to the synthesis of Scheme 9: Pictet-Spengler reactions between amines and aldehydes or ketones in HFIP A wide range of aromatic aldehydes, regardless of electron-withdrawing or electron-donating substituents on the aromatic ring, the reactions could give the tetrahydro-β-carboline products in excellent yields.…”
Section: And Hfipmentioning
confidence: 99%
“…Therefore, the search continues for a better catalyst for the synthesis of pyrans in terms of operational simplicity, reusability, economic viability, and greater selectivity. The use of fluorinated solvent, as chemical reaction media in place of conventional volatile organic solvents, has grown dramatically in recent years [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Fluorinated alcohols possess interesting physiochemical properties, which include lower boiling points and higher melting points than their non-fluorinated counterparts, high polarity, strong hydrogen bond donation properties and the ability to solvate water.…”
Section: Introductionmentioning
confidence: 99%